2012
DOI: 10.3390/ijms131114679
|View full text |Cite
|
Sign up to set email alerts
|

Dual Bioactivities of Essential Oil Extracted from the Leaves of Artemisia argyi as an Antimelanogenic versus Antioxidant Agent and Chemical Composition Analysis by GC/MS

Abstract: The study was aimed at investigating the antimelanogenic and antioxidant properties of essential oil when extracted from the leaves of Artemisia argyi, then analyzing the chemical composition of the essential oil. The inhibitory effect of the essential oil on melanogenesis was evaluated by a mushroom tyrosinase activity assay and B16F10 melanoma cell model. The antioxidant capacity of the essential oil was assayed by spectrophotometric analysis, and the volatile chemical composition of the essential oil was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 62 publications
2
54
1
Order By: Relevance
“…These results indicated that down-regulation of JAK/STAT signaling activation is a possible mechanism for AAEO to inhibit LPS-induced iNOS and COX-2 gene expression as well as the production of some pro-inflammatory cytokines and chemokines in macrophages. Moreover, since essential oil possesses antioxidant activity for scavenging ROS (Miguel, 2010, Huang et al, 2012, and the production of ROS is a key step involved in JAK/STATs activation in macrophages (Simon et al, 1998), it is plausible that AAEO inhibits JAK/STATs signaling by ROS scavenging. It is of interest to note that AAEO dose-dependently reduced LPS-induced ROS production in RAW264.7 macrophages, which implicates the inhibitory effect of AAEO on JAK/STATs might be attributed to its antioxidant activity toward ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that down-regulation of JAK/STAT signaling activation is a possible mechanism for AAEO to inhibit LPS-induced iNOS and COX-2 gene expression as well as the production of some pro-inflammatory cytokines and chemokines in macrophages. Moreover, since essential oil possesses antioxidant activity for scavenging ROS (Miguel, 2010, Huang et al, 2012, and the production of ROS is a key step involved in JAK/STATs activation in macrophages (Simon et al, 1998), it is plausible that AAEO inhibits JAK/STATs signaling by ROS scavenging. It is of interest to note that AAEO dose-dependently reduced LPS-induced ROS production in RAW264.7 macrophages, which implicates the inhibitory effect of AAEO on JAK/STATs might be attributed to its antioxidant activity toward ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Dried leaves of this herb are also used in acupuncture clinics in China to treat various diseases, especially chronic conditions such as osteoarthritis, asthma, gastrointestinal disorders, and insomnia (Ge et al, 2016). A. argyi is reported to possess multiple pharmacological activities including anti-inflammatory, antimicrobial, antiasthma, analgesic, antivirus, antioxidant, antitumor and immunomodulatory effects (Jiang et al, 2005;Ge et al, 2016;Huang et al, 2012;Bao et al, 2013;), most of which are contributed by the essential oil existing in A. argyi leaves. Though the anti-inflammatory activity of Artemisia genus has been studied intensively and several anti-inflammatory compounds were also found in this plant (Moscatelli et al, 2006;Min et al, 2009;Choi et al, 2013;Habib and Waheed, 2013;Jeong et al, 2014;Park et al, 2015;Zeng et al, 2014), there is no much substantial evidence supporting the anti-inflammatory property of this herbal medicine and the molecular targets for the effects still remain unclear, which limited its application into clinical practice.…”
Section: Introductionmentioning
confidence: 98%
“…Lycogen™ are available from Asia-Pacific Biotech Developing, Inc. (Kaohsiung, Taiwan). Murine B16F10 cells are cultured in Dulbecco’s modified Eagle’s medium containing 10% fetal bovine serum, 1% glutamine and 50 μg/mL gentamicin at 37 °C in 5% CO 2 [11,12]. Adult zebrafish were obtained from a commercial dealer, and 10–15 fishes were kept in a 5 L acrylic tank with the following conditions; 28.5 °C, with a 14/10 h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Artemisiae argyi Folium (the dried leaves of Artemisia argyi H. Léveillé & Vaniot) and Artemisiae lavandulaefoliae Folium (the dried leaves of Artemisia lavandulifolia Candolle), two morphologically similar herbal medicines derived from Artemisia genus, are widely used in China and East Asia for treatment of haemorrhage, pain, eczema, and menstruation‐related symptoms . In clinic, these two herbal medicines have been extensively used due to various pharmacological functions, including anti‐bacterial, anti‐inflammatory, antioxidant, anti‐cancer, haemostatic and analgesic activities . Intriguingly, the two herbal medicines derived from the Artemisia genus have similar morphological effects, but the pharmacological effects and clinical applications are different.…”
Section: Introductionmentioning
confidence: 99%
“…2 In clinic, these two herbal medicines have been extensively used due to various pharmacological functions, including anti-bacterial, anti-inflammatory, antioxidant, anti-cancer, haemostatic and analgesic activities. [3][4][5][6] Intriguingly, the two herbal medicines derived from the Artemisia genus have similar morphological effects, but the pharmacological effects and clinical applications are different. According to the theory of traditional Chinese medicine, Artemisiae argyi Folium was reported to possess immuno-modulatory properties and commonly used for treatment of haemorrhage, pain, and skin itch, while Artemisiae lavandulaefoliae Folium has remarkable effects on menstruationrelated symptoms and was usually used in curing Gong cold infertility and irregular menstruation.…”
Section: Introductionmentioning
confidence: 99%